Football in Africa : conflict, conciliation and community / edited by Gary Armstrong and Richard Giulianotti. - Armstrong, Gary, 1960-; Giulianotti, Richard, 1966- (Palgrave Macmillan, 2004)
A detailed social analysis of football within Africa. It features case-study essays that draw heavily on detailed fieldwork to examine the distinctive football cultures that have grown up in African communities.